The effect of Footsteps Total to Long Labor - Ririn Wahyu Hidayati (JHeS (Journal of Health Studies), 2018)
Quantitative research aims to demonstrate the effect of footsteps for 4 weeks at the third trimester pregnant women to the long labor. Analysis with normality test and Mann Whitney. Therefore, the research proves that the third trimester pregnant women who walk ≥5,697 steps/day have a labor time stage I, II and the total of labor are shorter than the third trimester pregnant women who walk 5,697 steps/day (p=0.0001). The conclusion from this study is footsteps affects the duration of labor. Pregnant women at least walk 5,697 steps/day to shorter labor duration.